Arundic Acid (ONO-2506), an Inhibitor of S100B Protein Synthesis, Prevents Neurological Deficits and Brain Tissue Damage Following Intracerebral Hemorrhage in Male Wistar Rats. (1st August 2020) - Cordeiro, J.L.; Neves, J.D.; Vizuete, A.F.; Aristimunha, D.; Pedroso, T.A.; Sanches, E.F.; Gonçalves, C.A.; Netto, C.A.
Highlights: Arundic acid reduced S100B levels after intracerebral hemorrhage. Arundic acid prevented excessive astrocytic activation in the damaged striatum. Arundic acid reduced cellular death and enhanced neuronal survival in injured rats. Arundic acid enhanced brain antioxidant defenses. Arundic acid reversed neurological deficits and tissue damage after the injury. Abstract: Stroke is one of the leading causes of mortality and neurological morbidity. Intracerebral hemorrhage (ICH) has the poorest prognosis among all stroke subtypes and no treatment has been effective in improving outcomes. Following ICH, the observed high levels of S100B protein have been associated with worsening of injury and neurological deficits. Arundic acid (AA) exerts neuroprotective effects through inhibition of astrocytic synthesis of S100B in some models of experimental brain injury; however, it has not been studied in ICH. The aim of this study was to evaluate the effects of intracerebroventricular (ICV) administration of AA in male Wistar rats submitted to ICH model assessing the following variables: reactive astrogliosis, S100B levels, antioxidant defenses, cell death, lesion extension and neurological function. Firstly, AA was injected at different doses (0.02, 0.2, 2 and 20 μg/μl) in the left lateral ventricle in order to observe which dose would decrease GFAP and S100B striatal levels in non-injured rats. Following determination of the effective dose, ICH damage was induced by IV-S collagenase intrastrial injection and 2 μg/μl AA was injected through ICV route immediately before injury. AA treatment prevented ICH-induced neurological deficits and tissue damage, inhibited excessive astrocytic activation and cellular apoptosis, reduced peripheral and central S100B levels (in striatum, serum and cerebrospinal fluid), improved neuronal survival and enhanced the antioxidant defences after injury. Altogether, these results suggest that S100B is a viable target for treating ICH and highlight AA as an interesting strategy for improving neurological outcome after experimental brain hemorrhage.